Effects of massage as a recuperative technique on autonomic modulation of heart rate and cardiorespiratory parameters: A study protocol for a randomized clinical trial - Mantovani Junior, Nilton [UNESP]; Pizzo Junior, Eduardo [UNESP]; dos Santos Siqueira, Malu [UNESP]; de Souza Cavina, Allysiê Priscilla [UNESP]; Pastre, Carlos Marcelo [UNESP]; Marques Vanderlei, Franciele [UNESP] (Springer Nature, 2018)
Background: Recuperative techniques have been used to anticipate and potentiate recovery. The massage is one of the most widely used in sports. Among the ways to demonstrate the recovery of the organism is the resumption of autonomic modulation of heart rate, which can be analyzed in situations that cause disturbances in the behavior of the cardiovascular system with the objective of verifying the responsiveness of the autonomic nervous system (ANS). Recovery can be assessed through heart rate variability (HRV) which analyzes the oscillations in consecutive heartbeats, thus allowing an important non-invasive alternative for the study of modulation of the ANS. The objective of the study will be to measure the effects of massage as a recuperative technique on the autonomic modulation of heart rate and cardiorespiratory parameters at different moments of application. Methods: This is a randomized, cross-over clinical trial. Forty men aged 18 to 30years, healthy and physically active according to the International Physical Activity Questionnaire will participate in the study. Participants will be randomized into groups, which will perform the five interventions of the study at randomized moments, one intervention per session: Intervention 1: control; Intervention 2: participants will receive the massage protocol; Intervention 3: performance of the stress protocol; Intervention 4: participants will perform the stress protocol and immediately after receive the massage; Intervention 5: participants will perform the stress protocol and 1 h after conclusion of the protocol will receive the massage. The sessions will occur with an interval of 1 week between them and, due to the technique used, blinding participants and therapists is not possible. The primary outcome measure is HRV that will be measured 2 h after the conclusion of each intervention, and secondary outcome measures, which include heart rate, respiratory rate, blood pressure, oxygen saturation, and individual touch perception, will be measured at specific moments in the course of each intervention. Discussion: The implementation and use of this standardized protocol should provide important and reliable information regarding the use of massage in post-exercise recovery, with the identification of its effects on the ANS and the best timing and form of massage application. The data obtained in the present study will provide subsidies for the best management of application of the technique in sports clinical practice, considering periods of training and, mainly, of competitions.
Keywords: Autonomic nervous system; Heart rate; Massage; Recovery of function